PENGGUNAAN METFORMIN PADA PASIEN POLYCYSTIC OVARY SYNDROME (PCOS) - Salasanti, Citra Dewi; Agustini, Dewi Darwati; Ramdani, Amalia Dewi (Jurnal Buana Farma, 2024)
Infertility in women of reproductive age with Polycystic Ovary Syndrome (PCOS) in Indonesia is increasing. Insulin resistance occurs in some PCOS patients, so the use of insulin sensitivity-enhancing drugs such as metformin is recommended. This study was conducted to determine the use of metformin in PCOS patients at independent doctor's practices in Bandung City. The study was conducted as an observational descriptive study with data collected retrospectively using purposive sampling. Data were taken from patient medical records and interviews with the doctor in charge. The sample in this study consisted of patients who met the inclusion and exclusion criteria. The data obtained were then summarized and displayed in table form. The results showed that the majority of PCOS patients were 26-30 years old with marriages that had lasted for 3 years. Ovulation and pregnancy in PCOS patients who used oral metformin treatment occurred in 15% of cases. The metformin used had a dose of 500-850 mg, which was given twice a day for 4-9 months.